1999
DOI: 10.1017/s1355838299981475
|View full text |Cite
|
Sign up to set email alerts
|

The yeast Saccharomyces cerevisiae YDL112w ORF encodes the putative 2′-O-ribose methyltransferase catalyzing the formation of Gm18 in tRNAs

Abstract: The protein sequences of three known RNA 29-O-ribose methylases were used as probes for detecting putative homologs through iterative searches of genomic databases. We have identified 45 new positive Open Reading Frames (ORFs), mostly in prokaryotic genomes. Five complete eukaryotic ORFs were also detected, among which was a single ORF (YDL112w) in the yeast Saccharomyces cerevisiae genome. After genetic depletion of YDL112w, we observed a specific defect in tRNA ribose methylation, with the complete disappear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 76 publications
1
109
0
Order By: Relevance
“…This suggests that there are other determinants for this and other modifications, including dihydrouri- dine modification in other organisms. Interestingly, mutations in tRNA Ser (G18C and G19C, separately) not only abolished Gm 18 modification but also blocked the formation of D 20 in tRNA Ser , suggesting the dependence of the tertiary structure for D 20 modification (28).…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that there are other determinants for this and other modifications, including dihydrouri- dine modification in other organisms. Interestingly, mutations in tRNA Ser (G18C and G19C, separately) not only abolished Gm 18 modification but also blocked the formation of D 20 in tRNA Ser , suggesting the dependence of the tertiary structure for D 20 modification (28).…”
Section: Discussionmentioning
confidence: 97%
“…There is no obvious homology with other methyltransferases, based on BLAST search. Moreover, there is little, if any, similarity between Trm13 protein and other tRNA 29-O-methyltransferases identified in yeast (Cavaille et al 1999;Pintard et al 2002a,b;Lapeyre and Purushothaman 2004), as determined by pairwise BLAST, or with the RrmJ/fibrillarin superfamily of 29-Omethyltransferases (Feder et al 2003). Since Trm13 protein is described in the PFAM database as a domain of unknown function (DUF 715) and all of the putative Trm13 protein homologs are annotated as novel or hypothetical proteins, the Trm13 family might represent an additional family of methyltransferase proteins, although the low degree of similarity among methyltransferases within the family precludes a definitive statement in this regard (Schubert et al 2003).…”
Section: Trm13 Protein Is Highly Conserved Within Eukaryotes and Is Nmentioning
confidence: 99%
“…Trm7 methylates the ribose at positions 32 and 34 of three tRNAs, and trm7 mutants have an important role in translational fidelity (Pintard et al 2002b). Trm3 modifies G 18 on 10 of the 34 sequenced tRNAs (Cavaille et al 1999), and, like many other modification proteins that act at remote sites from the anticodon (Hopper and Phizicky 2003), disruption of the gene has little obvious effect on growth or translation (Cavaille et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Lhp1 protein has been proposed to function as an RNA chaperone facilitating endonucleolytic trimming of the 39 trailers of pre-tRNAs (Yoo & Wolin, 1997)+ In fact, a mutation in the sup61 gene (sup61-10 ) located at position 28 of the tRNA was previously shown to be lethal in combination with a disruption of the LHP1 gene+ When Lhp1 was depleted from sup61-10 cells, a decrease in partially processed as well as mature tRNA CGA Ser was seen (Yoo & Wolin, 1997)+ The similarity in phenotypes and the fact that a catalytically inactive Trm2p suppressed the phenotype of the sup61-T51C trm2 strain prompted us to investigate the role of Lhp1p in the sup61 mutant strains isolated by us+ The Lhp1 protein has, to our knowledge, no tRNA modification activity+ Moreover, we could not detect any apparent difference in modified nucleosides between a wild-type and a lhp1 strain in HPLC analysis of total tRNA (data not shown)+ The sup61-T51C, sup61-T44G, sup61-T47:2C, and sup61-T20A alleles were combined with a lhp1 disruption and the resulting sup61 lhp1 double mutant strains behaved like the sup61 trm2 strains, that is, viable at 25 8C but inviable or very slow growing at 30 8C (Fig+ 5)+ We also investigated the previously identified sup61-10 allele (Yoo & Wolin, 1997) for genetic interaction with a trm2 null allele and a sup61-10 trm2 double mutant was inviable at 30 8C (data not shown)+ These data indicated similar functions of the Trm2 and Lhp1 proteins with respect to stabilization of tRNA during maturation+ However, a trm2 lhp1 double mutant strain was viable with no obvious growth defect and the processing pattern of tRNA CGA Ser in the trm2 lhp1 strain was identical to that of the single lhp1 mutant (data not shown; Yoo & Wolin, 1997)+ This suggested that the Trm2p and Lhp1p did not have redundant functions, but rather that both proteins were essential in the maturation process of mutant tRNA CGA Ser + It seemed possible that removal of any gene encoding a protein interacting with tRNA CGA Ser in the maturation process would lead to a synergistic phenotype with the various mutant sup61 alleles+ To investigate this hypothesis, the sup61-T51C, sup61-T44G, sup61-T47:2C, and sup61-T20A alleles were combined with null alleles of PUS4, TRM1, and TRM3 encoding pseudo- (Becker et al+, 1997), tRNA (m 2 2 G 26 )dimethyltransferase (Ellis et al+, 1986), and tRNA(Gm 18 ) 29-O-ribose methyltransferase (Cavaille et al+, 1999), respectively+ Precursor tRNA CGA Ser has m 2 2 G 26 and ⌿ 55 whereas Gm 18 is present only in the mature tRNA (Etcheverry et al+, 1979)+ A null allele of the RIT1 gene encoding a tRNA i…”
Section: Mjo Johansson and As Byströmmentioning
confidence: 99%